PENDEKATAN CONTEXTUAL TEACHING AND LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA MAHASISWA PGSD - Berta Apriza (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2019)
Approach involving students actively in constructing their own knowledge mathematics and make mathematics as the science which abstract science students real life. The Cintextual Teaching and Learning approach be taken to examine issues when processing learning, with way with real life according to can develop indicators can foster students ability to think.Analysis of students problems in improving students of critical thinking skills through the contextual teaching and learning by understanding the stages of the learning procces, not just to memorize the procedure of solving problems in learning but students can also knowledge that they have learned by linking exesting problems which is in real life, so that the knowledge students can be used in the long run.